Financial sector reforms and exchange arrangements in Eastern Europe - Calvo, Guillermo A....[et al] (IMF WashingtonUS, 1993)
Deals with two issues facing Eastern Europe viz. how to develop their financial sectors along market lines and what type of exchange arrangements to adopt.